Beauveria bassiana: a new N6-(2-hydroxyethyl)-adenosine–producing fungus - Kuanbo Liu; Fen Wang; Wenzhao Wang; Caihong Dong (Mycology, 2017)
N6-(2-Hydroxyethyl)-adenosine (HEA), which was the first calcium antagonist derived from biological sources, has been intensively investigated because of its ability to inhibit tumour cell proliferation, restrain inflammation, protect kidneys and function as a sedative and insecticide. Up to now, the production of HEA has been detected only in a few species such as Cordyceps pruinosa, C. militaris and Isaria tenuipes. Here, we found a new HEA-producing fungus, which was identified as Beauveria bassiana based on morphological and phylogenetic characteristics. The HEA production was verified by reversed-phase high-performance liquid chromatography/mass spectrometry in this fungus. Moreover, HEA was also detected in the mycelia of two other B. bassiana strains from different origins, but not in the culture medium of all tested B. bassiana strains. The maximum production of HEA (0.8483 ± 0.0439 mg/g mycelia dry weight) was achieved on day 7. The fungal biomass and kinetics of HEA production exhibited similar trends over the duration of the culture period. This is the first report describing HEA production in B. bassiana, which suggests that this fungal strain may have new applications as a source of HEA.